IMPLEMENTASI VIRTUAL TOUR SEDERHANA DALAM PENGENALAN KAMPUS POLITEKNIK PARIWISATA BALI DI MASA PANDEMI COVID-19 - M Tanggap Sasmita (Pusat penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2021)
The Bali Tourism Polytechnic has an annual agenda for campus introduction activities called the Tour De Campus in a series of Basic Professional Attitude Development activities. , but in 2020 tThese activities cannot be carried out directly on campus in 2020 due to pandemic COVID-19. With limited resources and considered important, a Virtual Tour was created to replace these activities. The method used in writing this article is descriptive method from the results of designing activities that are carried out and directly observed. The stages of this descriptive research method are Problem Analysis, Activity Design and Design, and Implementation. Most of the results of the evaluation of the virtual tour activities were satisfied with the activities carried out. This activity can be carried out again in the future by increasing the use of technology to make it more attractive and can be duplicated by schools / campuses / other institutions that have technological limitations.